أثر الإبداع التسويقي على تنافسية المؤسسة . - طافر ., زهير; مولفرعة, فاطمة الزهراء (جامعة الوادي- University of Eloued, 2017)
Attention to marketing innovation enables the achievement of long-term strategic objectives, the most important of which is the achievement of continuous competitive advantages. The attempt to develop through the adoption of marketing innovation as an alternative strategic, in order to possess the competitive advantages of a high degree that qualify the institution to compete and withstand the current and future challenges imposed by other institutions. The accreditation and adoption of creativity in the marketing mix offers opportunities that are not available to others. It opens up the prospects of owning a competitive advantage that is not owned by others. It also attracts and keeps more customers and gives them fame and reputation, in addition to the continuous improvement of performance, the achievement of a high degree of efficiency and getting returns and profits which is among the main objectives of any institution.
The impact of marketing creativity on the competitiveness of the enterprise
مقال
Keywords: Enterprise, Marketing Innovation, Competitiveness, Competitive Advantage, Market, Competition.